Research Progress on the Formation Mechanism and DNA Methylation of Autologous Arteriovenous Fistula Stenosis - Zou, Zhi; Zhao, Yanlong (Journal of Contemporary Medical Practice, 2025)
Arteriovenous fistula (AVF), as the most commonly used vascular pathway for end-stage renal failure hemodialysis patients, is also the premise for hemodialysis patients to start and maintain dialysis, but its complications have become the main factors affecting hospitalization and death of dialysis patients. The most common complication of AVF is intimal hyperplasia resulting in stenosis. In order to better prevent and treat AVF stenosis, it is of great significance to further study the mechanism of its occurrence and development for HD patients. The mechanism of AVF stenosis is the result of the interaction of multiple factors, and a deeper understanding of these mechanisms can help to develop more effective diagnostic and treatment strategies to improve the patency of AVF in HD patients. This article briefly describes the mechanism of AVF formation and the progress of DNA methylation research, hoping to provide new prevention and treatment ideas for further clinical research and practice, and finally achieve the purpose of improving the quality of life of HD patients.